2009
DOI: 10.1002/cbic.200900044
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Oxime Oligomers Inhibit Alzheimer's Amyloid Fibril Formation and Disaggregate Fibrils In Vitro

Abstract: See you later amyloid beta: A screen of a small library of oxime oligomers with an HTS fluorescence assay for amyloid fibril inhibition and subsequent investigation by atomic force microscopy revealed two new micromolar inhibitors of amyloid fibril formation. These new inhibitors have IC(50) values in the 10 microM range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…The design of novel polyphenol‐based or polyphenol‐inspired drugs against specific protein targets thus constitutes another promising direction for future research on polyphenols. Plant polyphenols have already started to inspire academic scientists in their quest for novel anticancer agents, more powerful natural product‐like antioxidants for use, for example, as food preservatives, and antifibrillogenic agents for the fight against neurodegenerative pathologies, as well as various functionalized materials that take advantage of the unique physicochemical properties of the phenol functional group 167. Many more exciting developments are certainly around the corner.…”
Section: What About the Future? Remaining Challenges …︁mentioning
confidence: 99%
“…The design of novel polyphenol‐based or polyphenol‐inspired drugs against specific protein targets thus constitutes another promising direction for future research on polyphenols. Plant polyphenols have already started to inspire academic scientists in their quest for novel anticancer agents, more powerful natural product‐like antioxidants for use, for example, as food preservatives, and antifibrillogenic agents for the fight against neurodegenerative pathologies, as well as various functionalized materials that take advantage of the unique physicochemical properties of the phenol functional group 167. Many more exciting developments are certainly around the corner.…”
Section: What About the Future? Remaining Challenges …︁mentioning
confidence: 99%
“…Tetracycline(s) showed anti-amyloidogenic activity in vitro [1051] and protected Caenorhabditis elegans from A␤-induced toxicity by targeting oligomers [1052]. [745,1043,1095,1096,[1097][1098][1099][1100][1101][1102][1103][1104][1105] 2009: [1106][1107][1108][1109][1110][1111][1112][1113], 2010: [391,551,980,[1114][1115][1116][1117], 2011: [549,643,[1118][1119][1120][1121][1122] and 2012: [1033,[1123][1124][1125][1126][1127][1128][1129]1728].…”
Section: Drugs Preventing Amyloid-␤ Aggregationmentioning
confidence: 99%
“…As a consequence, considerable effort has been directed toward the identification of the substances able to reduce amyloid aggregation. In the past few years, a range of diverse small molecules have been found to inhibit or reduce the amyloid aggregation of various proteins, particularly in relation to Aβ deposition, the aggregation of transthyretin and the formation of protease-resistant forms of the prion protein [90-94]. Kim [93] investigated the effect of several classes of naturally occurring compounds on Aβ amyloid aggregation.…”
Section: Tacrine and Anti-amyloid Aggregationmentioning
confidence: 99%
“…Doplhin et al . [94] demonstrated that longer trioxime oligomers showed an effective reduction of Aβ amyloid fibrils formation. One of the first compounds to be identified with blocked tau-tau interaction was the phenothiazine methylene blue [95].…”
Section: Tacrine and Anti-amyloid Aggregationmentioning
confidence: 99%